EVALUASI BIAYA KEMOTERAPI PASIEN EARLY BREAST CANCER DI RSUD TUGUREJO SEMARANG PERIODE JULI-DESEMBER 2018 - Wilis Rakhmadhanti; Fef Rukminingsih (Prodi D3 Farmasi Politeknik Katolik Mangunwijaya, 2022)
Early breast cancer (EBC) is defined as with or without in a breast cancer, but it has not metastasized to wider tissue. Chemotherapy expense has 59% portion of the total cost of cander patients at the hospital. There were 137 EBC patients visit during January-March 2018 conducted at Tugurejo Regional Hospital Semarang. Therefore, research is needed to evaluate the cost of chemotherapy in EBC patient in Tugurejo Hospital Semarang. This study was an observational descriptive study with a cross sectional study design. Data sources were gained from Medical Record (MR) data and billing / billing data for National Health Insurance (JKN) participant patients with an EBC diagnosis undergoing chemotherapy at Tugurejo Hospital Semarang in the period July-December 2018. The inclusion criteria for this study was JKN patients with EBC diagnosis age 17 -65 years who did chemotherapy at Tugurejo General Hospital Semarang in the period July-December 2018. Data was processed qualitatively and quantitatively. The results of evaluation of the cost of chemotherapy for EBC patients at Tugurejo Hospital Semarang in the period July-December 2018 were done with the regimen Doxorubicin-Doxetacel-Fluorouracil (AT-F) Rp 3.683.388,00 ± 193.960, Doxetacel-Epirubicin-Fluorouracil (TE-F) Rp 4.342.914 00 ± 37.614, Fluorouracil-Epirubicin-Cyclofosphamid (FEC) Rp 2.929.464,00 ± 193.960, Fluorouracil-Doxorubicin-Cyclofosphamid (FAC) amounting to Rp2.471.671,00 ± 193.960.